Defining the Power and Energy Demands from Ships at Anchorage for Offshore Power Supply Solutions - Nikolaos P. Ventikos; Panagiotis Sotiralis; Manolis Annetis; Marios-Anestis Koimtzoglou; Lina Keratsa (Energies)
The maritime industry, following several conventions, regulations, and initiatives, is trying to adapt and limit its GHG and other local polluting emissions. A crucial aspect of these decarbonisation efforts is the provision of electric energy to vessels, either in port or stationed at anchorages. The latter prevents the option of receiving shore power to support their needs without operating their generators. Research and innovation efforts are attempting to fill this gap through several technology options. This study focuses on the systematic definition of the power and energy demands at anchorage to drive the design of such solutions, focusing on the materialisation of a modular and scalable power barge serving as an offshore power supply solution. Data for various ports and ship types were collected and analysed properly to extract significant insights. Results formulated baselines, per ship type and port, to be used for selecting power modules’ configurations and meeting these demands. This study, considering the lack of industry data regarding power demand, relies on existing studies, guidelines, and other literature to define power demand, which in turn introduces a great deal of uncertainty. Thus, a detailed statistical analysis was employed, together with probability modelling, in order to limit the uncertainty and provide a baseline for the power and energy demands to be verified by future studies capitalising on the accumulation of actual industry data.